(untitled) (Advancements in Homeopathic Research, 2022)
Objectives: Hypothyroidism is a well-known disease worldwide. But use of thyroxin in large doses may produce severe side effects & that’s why it is a need of the era to find out alternative therapy to combat such type of endocrinal disorder. Methods: A case study was done in a Govt. Homeopathic hospital in west Bengal in O.P.D. for 9 months (approx.). A 20yr old female patient Ms. T presented with symptoms like hypothyroidism which was confirmed by Thyroid profile (TSH- 139.74 microIU/Ml, T3- 0.23 ng/ mL,T4- 1.02 microgram/dL.).The similimum was selected after proper case recording & analysis of the symptoms as per Homeopathic philosophy & principles. The follow up of the case was done. Result: Gradually TSH level declined to normal level with disappearing of all the symptoms of the hypothyroidism.